Reduced amyloid‐β degradation in early Alzheimer's disease but not in the APPswePS1dE9 and 3xTg‐AD mouse models. Issue 3 (23rd April 2013) - Stargardt, Anita; Gillis, Judith; Kamphuis, Willem; Wiemhoefer, Anne; Kooijman, Lieneke; Raspe, Marcel; Benckhuijsen, Willemien; Drijfhout, Jan W.; M. Hol, Elly; Reits, Eric
Summary Alzheimer's disease (AD) is hallmarked by amyloid‐β (Aβ) peptides accumulation and aggregation in extracellular plaques, preceded by intracellular accumulation. We examined whether intracellular Aβ can be cleared by cytosolic peptidases and whether this capacity is affected during progression of sporadic AD (sAD) in humans and in the commonly used APPswePS1dE9 and 3xTg‐AD mouse models. A quenched Aβ peptide that becomes fluorescent upon degradation was used to screen for Aβ‐degrading cytoplasmic peptidases cleaving the aggregation‐prone KLVFF region of the peptide. In addition, this quenched peptide was used to analyze Aβ‐degrading capacity in the hippocampus of sAD patients with different Braak stages as well as APPswePS1dE9 and 3xTg‐AD mice. Insulin‐degrading enzyme (IDE) was found to be the main peptidase that degrades cytoplasmic, monomeric Aβ. Oligomerization of Aβ prevents its clearance by IDE. Intriguingly, the Aβ‐degrading capacity decreases already during the earliest Braak stages of sAD, and this decline correlates with IDE protein levels, but not with mRNA levels. This suggests that decreased IDE levels could contribute to early sAD. In contrast to the human data, the commonly used APPswePS1dE9 and 3xTg‐AD mouse models do not show altered Aβ degradation and IDE levels with AD progression, raising doubts whether mouse models that overproduce Aβ peptides are representative for human sAD.